Nutrition disparities and the global burden of malnutrition. (13th June 2018) - Perez-Escamilla, Rafael; Bermudez, Odilia; Buccini, Gabriela Santos; Kumanyika, Shiriki; Lutter, Chessa K; Monsivais, Pablo; Victora, Cesar
Abstract : Strategies to tackle stunting, obesity, and micronutrient deficiencies must take into account the inequities in which these diseases are rooted, argue Rafael Perez-Escamilla and colleagues